Widespread ancient whole-genome duplications in Malpighiales coincide with Eocene global climatic upheaval - Cai, Liming; Xi, Zhenxiang; Amorim, André M.; Sugumaran, Manickam; Rest, Joshua S.; Liu, Liang; Davis, Charles C. (Wiley, 2018)
Whole-genome duplications (WGDs) are widespread and prevalent in vascular plants and frequently coincide with major episodes of global and climatic upheaval, including the mass extinction at the Cretaceous–Tertiary boundary (c. 65 Ma) and during more recent periods of global aridification in the Miocene (c. 10–5 Ma). Here, we explore WGDs in the diverse flowering plant clade Malpighiales. Using transcriptomes and complete genomes from 42 species, we applied a multipronged phylogenomic pipeline to identify, locate, and determine the age of WGDs in Malpighiales using three means of inference: distributions of synonymous substitutions per synonymous site (Ks) among paralogs, phylogenomic (gene tree) reconciliation, and a likelihood-based gene-count method. We conservatively identify 22 ancient WGDs, widely distributed across Malpighiales subclades. Importantly, these events are clustered around the Eocene–Paleocene transition (c. 54 Ma), during which time the planet was warmer and wetter than any period in the Cenozoic. These results establish that the Eocene Climatic Optimum likely represents a previously unrecognized period of prolific WGDs in plants, and lends further support to the hypothesis that polyploidization promotes adaptation and enhances plant survival during episodes of global change, especially for tropical organisms like Malpighiales, which have tight thermal tolerances.